Dynamics throughout a complete surge of Iceberg Glacier on western Axel Heiberg Island, Canadian High Arctic - Benoît Lauzon; Luke Copland; Wesley Van Wychen; William Kochtitzky; Robert McNabb; Dorthe Dahl-Jensen (Journal of Glaciology, 2023)
This study provides the first comprehensive reconstruction of the dynamics of Iceberg Glacier, located on western Axel Heiberg Island, and reveals detailed observations of a complete surge for the first time in the Canadian Arctic. Historical aerial photographs, declassified intelligence satellite photographs, optical satellite imagery and synthetic aperture radar data were used to quantify changes in terminus position, ice velocity and glacier thickness since the 1950s. A surge initiated at the terminus in 1981 and terminated in 2003, suggesting a 22-year active phase. High surface velocities, reaching ~2300 m a−1 in 1991, were accompanied by a maximum terminus advance of >7 km and a large transfer of mass down-glacier, causing significant median trunk-wide surface elevation changes attaining >3 ± 1 m a−1. We suggest that the retreat from a pinning point, flotation of the terminus, the removal of sea-ice from the ice front, and an increase in subglacial meltwater availability from relatively high air temperatures in 1981 likely contributed to surge initiation. The ensuing quiescent period has seen a continual decrease in surface flow rates to an average centreline velocity of 11.5 m a−1 in 2020–21, a gradual steepening of the glacier surface and a > 2.5 km terminus retreat.